Evaluation of the relative effectiveness of the 2017 updated Manchester scoring system for predicting BRCA1/2 mutations in a Southeast Asian country. Issue 5 (23rd December 2017) - Chew, Winston; Moorakonda, Rajesh Babu; Courtney, Eliza; Soh, Hazel; Li, Shao Tzu; Chen, Yanni; Shaw, Tarryn; Allen, John Carson; Evans, Dafydd Gareth R; Ngeow, Joanne
Abstract : Background: Germline mutations in the BRCA 1 and BRCA 2 genes have significant clinical implications for both risk-reducing and early surveillance management. The third and most recent revision of the Manchester scoring system (MSS3) used to distinguish patients indicated for germline BRCA1/2 testing included further adjustments for triple negative breast cancer, high-grade serous ovarian cancer and human epidermal growth factor 2 (HER2) receptor status. This study aims to evaluate the relative effectiveness of MSS3 in a Southeast Asian population. Methods: All patients in our centre were tested using next-generation sequencing (NGS) panels that included full gene sequencing as well as coverage for large deletions/duplications in BRCA1/2 . We calculated MSS1-3 scores for index patients between 2014 and 2017 who had undergone BRCA1/2 genetic testing and recorded their genetic test results. MSS1-3 outcomes were compared using receiver operating characteristic analysis, while associations with predictors were investigated using Fisher's exact test and logistics regression. Calculations were performed using Medcalc17. Results: Of the 330 included patients, 47 (14.2%) were found to have a germline mutation in BRCA1 or BRCA2 . A positive HER2 receptor was associated with a lower likelihood of a BRCA1/2 mutation (OR=0.125, 95% CI 0.016 to 0.955; P=0.007), while high-grade serous ovarian cancer was conversely associated with an increased likelihood of a BRCA1/2 mutation (OR=5.128, 95% CI 1.431 to 18.370; P=0.012). At the 10% threshold, 43.0% (142/330) of patients were indicated for testing under MSS3, compared with 35.8% (118/330) for MSS1% and 36.4% (120/330) for MSS2. At the 10% threshold, MSS3 sensitivity was 91.5% and specificity 65.0%, significantly better than the previous MSS1 (P = 0.037) and MSS2 (P = 0.032) models. Conclusion: Our results indicate that the updated MSS3 outperforms previous iterations and relative to the Manchester population, is just as effective in identifying patients with BRCA1/2 mutations in a Southeast Asian population.